2015
DOI: 10.1007/978-3-319-22723-8_53
|View full text |Cite
|
Sign up to set email alerts
|

Dual Camera Magic Lens for Handheld AR Sketching

Abstract: Abstract.One challenge of supporting in-situ sketching tasks with Magic Lenses on handheld Augmented Reality systems is to provide accurate and robust pose tracking without disrupting the sketching experience. Typical tracking approaches rely on the back-facing camera both for tracking and providing the view of the physical scene. This typically requires a fiducial to be in the scene which can disrupt the sketching experience on a blank sheet of paper [3]. We address this challenge by proposing a Dual Camera M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
1
1
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 8 publications
2
4
0
Order By: Relevance
“…This is also supported by the fact that none of participants found it difficult to look through the phone while virtually tracing, even though the task completion time took more than 10 minutes on average. These finding are also in line with our previous study [4].…”
Section: How Effective Are Phones In Supporting User Sketching Througsupporting
confidence: 94%
See 3 more Smart Citations
“…This is also supported by the fact that none of participants found it difficult to look through the phone while virtually tracing, even though the task completion time took more than 10 minutes on average. These finding are also in line with our previous study [4].…”
Section: How Effective Are Phones In Supporting User Sketching Througsupporting
confidence: 94%
“…Hence, building a ML system where these limitations are not present is bound to signifi-cantly improve ML performance. This is in line with our previous study where such a system (dual-camera magic lens) was built and revealed it has potential to be both faster and lead to a higher perceived satisfaction compared to SP and ML [4].…”
Section: Magic Lens Vs Static Peepholesupporting
confidence: 91%
See 2 more Smart Citations
“…The study also indicated that UPR outperformed DPR in terms of accuracy, task completion time, subjective workload and preference. They later extended their investigations to specifically study the use of surrounding visual context in a map navigation task [7] and to sketching applications [18]. Pucihar et al also proposed a specific variation of UPR, called contact-view, which allows pseudo transparent rendering of documents when a smartphone lies directly on the document [17,16], achieving similar effects compared to proprietary solutions using transparent displays [12,13].…”
Section: Related Workmentioning
confidence: 99%